An association study of SERPINA1 gene polymorphisms with the risk of metabolic dysfunction-associated steatotic liver disease In an Iranian population: A preliminary case-control study - Samira Abdollahi; Abbas Sahebghadam Lotfi; Ramin Saravani; Hamed Taheri (Biochemistry and Biophysics Reports)
Background: Metabolic dysfunction-associated steatotic liver disease (MASLD) is a type of fat accumulation in the liver that can lead to cirrhosis and chronic liver disease. MASLD is recognized as the most frequent of liver-associated deaths worldwide. The SERPINA1 gene encodes a serine protease protein that plays a pivotal role in the pathogenesis of liver deficiencies. In this study, we aimed to evaluate the genetic association between rs6647 (M1), rs709932 (M2), and rs1303 (M3) variants in the SERPINA1 gene and the risk of MASLD in an Iranian population. Methods: In this case-control study, 120 patients affected by MASLD and 120 healthy subjects participated. The Nephelometry system measured serum levels of α1-antitrypsin (A1AT). Biochemical tests were conducted to assess serum levels of blood parameters using commercially available kits. DNA extraction was performed using the salting-out method, followed by the amplification refractory mutation system-polymerase chain reaction (ARMS-PCR) method for genotyping. Statistical analysis was performed by SPSS v16.0. Results: The findings showed that the rs6647 G allele significantly increased the risk of MASLD. The G allele in codominant, dominant, and over-dominant models caused an increase in the risk of MASLD. Additionally, the rs709932 T allele was more frequent among patients compared to healthy subjects and significantly enhanced the risk of MASLD. The T allele in the codominant and recessive models indicated a high risk for MASLD in our population. The G allele of rs1303 caused an enhancement in the mean serum levels of A1AT in the MASLD group. Conclusions: Our results show an association between SERPINA1 gene variants and the risk of MASLD. The rs6647 (M1) and rs709932 (M2) variants of the SERPINA1 gene increased the risk of disorder in our population.